From liability to opportunity: An institutional approach towards value-based land remediation. (March 2017) - Plant, Roel; Boydell, Spike; Prior, Jason; Chong, Joanne; Lederwasch, Aleta
The remediation of contaminated sites impacts on stakeholders in potentially beneficial ways, yet stakeholder dialogue has historically been focussed on costs, risk, liability, stigma, and other negatives. Shedding light on stakeholders' remediation values can help reform remediation policy towards more positive outcomes of site clean-up. We adopt institutional theory to elicit plural motivations and cognitive assumptions as embedded in stakeholders' expressions of remediation values, objectives, and outcomes. We explore in four case studies with varying size, complexity, cultural diversity, and geographical location (three in Australia, one in Fiji) how remediation values operate within remediation decisions. Our findings suggest that more than economic costs, liability, and risks are at play in decision-making on contaminated land. Our research confirmed that different socio-ethical, environmental and sustainability values are evaluated differently by different types of actors (site owners, regulators, auditors, residents, local government, consultants). We found that remediation values often shift in the course of a remediation decision-making process, suggesting learning and improved understanding. Remediation policy that better facilitates and aligns stakeholders' articulations of initial and emergent outcomes sought from site clean-up is likely to enhance both economic and social value outcomes of remediation. Further research is needed on how remediation policy could better incorporate remediation value dynamics in stakeholder consultation and engagement.